Online scheduling in Minimizing Makespan on Identical Parallel Processor with Release Date - Nordin, S.; Caccetta, Louis (Universiti Teknologi Malaysia * Fakulti Sains, 2014)
In this paper, we address a non-preemptive task scheduling problem with an objective function of minimizing the makespan. We consider online scheduling with release date on identical parallel processing system with centralized and no splitting structure. Multi-steps heuristic algorithms are proposed to solve this non-deterministic scheduling problem. A computational experiment is conducted to examine the effectiveness of the proposed multi-steps method in different size problem. The computational results show that all the proposed heuristics obtain good results with the gap between optimal solutions are less than 10% even for a large date set. The experiment is performed using Microsoft Visual C++ programming software in windows environment.